STABILITY OF INDONESIA'S ISLAMIC (SHARIA) FINANCIAL SYSTEM: FACING ENERGY PRICE SHOCKS AND INFLATION DUE TO THE CLOSURE OF THE STRAIT OF HORMUZ - Fransisca Dwi Ratnasari; Desvita Tiara Maharani; Najwa Jawahir Gholiyah; Tara Aulia Nabilatuzzahra; Amalia Nuril Hidayati (Universitas Budi Luhur, 2026)
Abstract: The closure of the Strait of Hormuz in 2026 caused disruptions to global energy shipping routes and had significant impacts on Indonesia's Islamic financial system stability. As an oil-importing country, Indonesia is highly vulnerable to world oil price fluctuations that increase production costs and create inflationary pressures. Indonesia's inflation reached 4.76 percent year-on-year in February 2026, with the housing, water, electricity, and fuel group reaching 16.19 percent, while electricity tariffs surged 86.96 percent. This research aims to comprehensively examine the impact of the global energy crisis on Indonesia's Islamic financial system stability, including analysis of energy price transmission to domestic inflation and its effects on Islamic banking. Using library research methodology, the study analyzes data from Bank Indonesia, the Financial Services Authority, the Central Statistics Agency, academic journals, and financial institution reports. Research findings show that rising energy prices have the potential to drive domestic inflation through a cost-push inflation mechanism, transmitted through production cost channels, the rupiah exchange rate, and imported commodity prices. The impact of inflation creates pressure on the Islamic financial system through increased cost of funds and non-performing financing risk, although Islamic banking performance data through March 2026 shows a Non-Performing Financing (NPF) ratio that remains manageable, at 2.28 percent (gross) and 0.87 percent (net). The Islamic financial system maintains stability through Islamic monetary instruments such as SBIS, Islamic fiscal policy through zakat and waqf, renewable energy diversification, and acceleration of Islamic fintech. In conclusion, the Islamic financial system with profit-sharing principles proves more adaptive in facing the crisis and contributes to national economic stability. Abstrak: Penutupan Selat Hormuz pada tahun 2026 menyebabkan gangguan terhadap jalur energi global dan berdampak signifikan terhadap stabilitas sistem keuangan syariah Indonesia. Sebagai negara importir minyak, Indonesia sangat rentan terhadap fluktuasi harga minyak dunia yang meningkatkan biaya produksi dan menciptakan tekanan inflasi. Inflasi Indonesia mencapai 4,76 persen year-on-year pada Februari 2026, dengan kelompok perumahan, air, listrik, dan bahan bakar mencapai 16,19 persen, sementara tarif listrik melonjak 86,96 persen. Penelitian ini bertujuan mengkaji dampak krisis energi global terhadap stabilitas sistem keuangan syariah Indonesia secara menyeluruh, mencakup analisis transmisi kenaikan harga energi ke inflasi domestik dan dampaknya terhadap perbankan syariah. Menggunakan metode studi kepustakaan, penelitian menganalisis data dari Bank Indonesia, Otoritas Jasa Keuangan, Badan Pusat Statistik, jurnal ilmiah, dan laporan lembaga keuangan. Hasil penelitian menunjukkan bahwa kenaikan harga energi berpotensi mendorong inflasi domestik melalui mekanisme cost-push inflation yang ditransmisikan melalui saluran biaya produksi, nilai tukar rupiah, dan harga komoditas impor. Dampak inflasi menciptakan tekanan pada sistem keuangan syariah melalui peningkatan biaya dana dan risiko pembiayaan bermasalah, meskipun data kinerja perbankan syariah hingga Maret 2026 menunjukkan rasio Non-Performing Financing (NPF) yang masih terjaga di level 2,28 persen (gross) dan 0,87 persen (net). Sistem keuangan syariah menjaga stabilitas melalui instrumen moneter syariah seperti SBIS, kebijakan fiskal syariah melalui zakat dan wakaf, diversifikasi energi terbarukan, dan akselerasi fintech syariah. Kesimpulannya, sistem keuangan syariah dengan prinsip bagi hasil terbukti lebih adaptif dalam menghadapi krisis dan berkontribusi pada stabilitas ekonomi nasional.